PENENTUAN KINERJA IRIGASI PADA 16 BANGUNAN UTAMA (SECARA SERI) DI DAERAH IRIGASI JILU, KABUPATEN MALANG - Sayekti, Rini Wahyu; Soetopo, Widandi; Agisaqma, La Ode (Fakultas Teknik, Universitas Brawijaya, 2012)
Irrigation is necessary in the management are of determining the existence of an effort to assess the performance of a Regionnal Irrigation that in the future can be evaluated for better performance. At the time Jilu Irrigation Region there are 16 irrigation and served the rice irrigation area of 992 ha.In this study of irrigation performance assessment of physical and non physical condition. Where the physical assassement include the condition of building ang irrigation channels on each network, where as the non physical assessment procedures include the application of cropping pattern and techniques of water. The techniques here is the uniformity of water delivery, water delivery efficiency, and adequacy. The data used is the physical data of buildings on time Jilu Irrigation Region, the Global Plan of planning, rainfall data 2001 to 2011, discharge data on intake in the year 2001 to 2011.The result on condition assessment of the Jilu Irrigation Region time overall result obtained for 72,6% obtained from the percentage of the physical condition of 78,09% the percentage of cropping pattern of the application of 64,582, and the percentage of assessment techniques for 75,358% of water, then from the results analysis is performed of determining the overall performance of irrigation.Based on standart guidelines regarding the performance of irrigation areas. Research and Development Center of Water Resources in 2003 mentions irrigation performance assessment result is good if > 70%, is enough if the results of the assessment range from 50% to 70% and said to be badly damaged or if the results of assessment < 50% . Of the parameters that already axists then the overall performance of the Jilu Irrigation Region time said to be good with the percentage value of 72,6%Keywords: assessment of physical, the application of cropping pattern, adequacy, the uniformity, water delivery efficiency, Research and Development Center of Water Resources.